GAMBARAN HIGIENE SANITASI DEPOT AIR MINUM ISI ULANG DAN KUALITAS AIR MINUM ISI ULANG SESUAI STANDAR MIKROBIOLOGI - Khairinnisa, Silmi Kaffah; Setiyono, Andik; Gustaman, Rian Arie (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2024)
Water has an important role in all living things, especially for humans. One of the most important uses of water for humans is the need for drinking. The source of drinking water for the community in the UPTD Puskesmas Mangkubumi working area almost entirely comes from refilled drinking water depots. The general objective of this study was to determine the description of the sanitary hygiene of refillable drinking water depots and the quality of refillable drinking water according to microbiological standards in the UPTD Mangkubumi Puskesmas working area. This study was descriptive observational with a cross-sectional design by conducting observations, interviews and laboratory tests. The DAMIU sample was the total population of 24 DAMIUs. The results of the study were compared with Permenkes RI Number 43 of 2014 and Permenkes RI Number 2 of 2023. The population in this study were all refillable drinking water depots in the working area of UPTD Puskesmas Mangkubumi. The results showed that of the 24 DAMIUs that were observed for drinking water depot sanitation hygiene, 11 DAMIUs did not meet the requirements, namely having a total score of 70. For drinking water quality according to microbiological standards, 4 DAMIUs contained E.coli and Total Coliform. Depot owners are expected to improve sanitary hygiene based on sanitation of premises, equipment, hygiene of handlers and raw water and drinking water, as well as periodically checking raw water and drinking water at least once a year.